The influence of hamstring autograft diameter on patient-reported functional scoresfollowing anterior cruciate ligament (ACL) reconstruction - Rhatomy, Sholahuddin; Widjaya, Muhammad; Ghazali, Said; Setyawan, Riky; Budhiparama, Nicolaas C. (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2019)
Anterior cruciate ligament (ACL) reconstruction using hamstring tendon autograft is a common procedure in orthopedic surgery to treat ACL rupture. Graft diameter is very important in successfulness of ACL reconstruction. The purpose of this study was to evaluate the influence of hamstring autograft diameter on patient-reported functional scores following ACL reconstruction. The diameter of grafts were collected retrospectively from medical records of the patients who underwent primary ACL reconstruction with hamstring autograft in the Soeradji Tirtonegoro General Hospital, Klaten, Central Java. The patient-reported functional scores data according to the International Knee Documentation Committee (IKDC) score and the Knee Injury and Osteoarthritis Outcome Score (KOOS) were collected by phone call interview from the patients after more than six months post-reconstruction. The comparison between graft diameter and patient-reported functional scores was analyzed by independent t test. A p<0.05 was considered significant.Thirty-two patients who fulfilled the inclusion and exclusion criteria were involved in the study who were divided into two groupswith 16 patients in each group i.e.Group 1 with graft diameter ≤8mm and Group 2 with graft diameter >8mm.The result showed significant difference in KOOS and IKDC score between the both groups (p<0.05). Patients who underwent ACL reconstructionwith graft diameter >8mm (Group 2) had higher KOOS and IKDC score compared to graft diameter ≤8mm (Group 1) (p<0.05). In conclusion, ACL reconstructionwith increased hamstring autograft diameter >8 mm associated with better patient-reported functional scores in 6 monthsfollow-up after ACL reconstruction.